Statistical mapping of quantitative trait loci controlling the time to first callusing in oil palm (elaeis guineensis Jacq.) tissue culture - Ting, Ngoot Chin; Cheah, Suan Choo; Ishak, Zamzuri; Tan, Soon Guan; Qamaruz Zaman, Faridah; Ithnin, Maizura (Universiti Putra Malaysia Press, 2006)
An additional 400 genetic markers (126 RFLPs, 274 AFLPs) were successfully mapped on the earlier developed linkage maps using 87 F1 progenies derived from Deli dura X Yangambi pisifera cross. This resulted in a denser map with coverage length of 1, 714cM and 1,225cM for pisifera and dura, respectively. Further exploration to searchfor quantitative trait loci (QTL) associated with time to first callusing (TFC) was carried out by Kosambi Interval Mapping using the computer program MapQTL Version 4. O. The tissue culture trait data showed a continuous distribution. In this paper; three likelihood QTLs were detected in pisifera and two QTLs in dura at 99% and 95% significant thresholds. These QTL locations can be designated as statistically significant for contributing to the variation of TFG. Therefore, the information points to a genomic loci affecting tissue culturability in oil palm.